Latin American conceptualism and the rereading of the work of Teresa Burga - Ruiz Pataro, Micaela (2021)
This work focuses its attention on the relationship between two processes: the first is the creation and development of the Latin American conceptualism category, and the second is the work of the artist Teresa Burga, specifically her conceptual work, and the critical fortune that said production has experienced in time. The purpose of this is to show how the work of art critics and researchers can influence the destiny of artists. By means of a chronological and comparative analysis of the two mentioned processes, the close relationship between the scope that the artistic work experiences, and the work that the specialists develop will be confirmed. The research, limited for the moment to one category, hopes to show in the future that, as in the case of Latin American conceptualism, there are numerous additional categories that have been decisive in the dissemination of Teresa Burga's artistic work.